Strategies in song translation: dubbing of audiovisual musical productions aimed at Spanish teenage audiences - Cruz-Durán, Belén (Language and the Media 2022, 2022)
Producers such as The Walt Disney Company revolutionised both the small and big screens by making the musical genre accessible to the youngest audiences and by creating mass phenomena during an era when the Internet was far from being what it is today. At the beginning of the xxi century, the demand for DVD and Blu-ray increased and the distributors discovered a lucrative source of income in this market: the sale of DVDs, Blu-ray, CDs containing the soundtrack, merchandising, concerts, etc. It has therefore been considered innovative to carry out a statistical study of the strategies used in the translation of the songs included in the DVD and Blu-ray dubbed versions of teenage audiovisual musical films in order to thus confirm the factors that influenced their translation and distribution in Spanish. For that reason, the research corpus of the present study is comprised of a selection of 32 films, which are the result of an exhaustive search, revision and delimitation of American musical films dated between 2001 and 2019 which were translated from English into Spanish. It should be pointed out that the films selected are mainly productions with teenage protagonists of pre-university age (of approximately 12 to 18 years). This delimitation makes it possible, on the one hand, to narrow down the corpus to a manageable number of productions and, on the other, to analyse the cultural context they are framed in from two perspectives: adolescents as final recipients and, at the same time, as protagonists of the scenes of the selected productions.
Keywords: Canciones; Traducción; Materiales audiovisuales; Cine; Adolescentes; Song translation; Audiovisual translation; Traducción de canciones; Traducción audiovisual; Películas adolescentes; Estrategias de traducción; Translation strategies; AVT training; Skopos; Proceso traductor; Translation process